Walking with Mother Nature: Mental Health Benefits of Regular Nature Walks for Women and Implications for Female Post-Secondary Students - Sarah McAllister (Canadian Journal for New Scholars in Education, 2025)
Today’s crisis in women’s mental health has ignited an interest in evidence-based practices for improving mental health, such as nature walks. However, further research is needed on women’s lived experiences while walking in nature. The purpose of this research was to explore a woman’s nature walk experiences and their perceived impact on her mental health. In this hermeneutic phenomenological study, a female participant’s nature walk experiences and the meaning they are given were unraveled. Sampling was purposeful and data were collected by through a phenomenological interview. Interpretative phenomenological analyses revealed that nature walks offer numerous mental health benefits, including greater happiness, serenity, mindfulness, awe, gratitude to nature, problem-solving, and creativity, as well as reduced negative affect and stress. Findings provide novel insights into the mechanisms underlying the relationship between nature walks and women’s mental health. Results are discussed in relation to extant mental health, ecotherapy, and positive education research.